Contribuições do pluralismo didático no ensino de ciências: uma pesquisa-ação com estudantes do ensino fundamental - Saccomori, Fernanda (2020)
When it is inserted in the educational field, it is common to find a school disconnected from life, abstract, formalistic, authoritarian and passive. In addition, there is still an authoritarian and arbitrary school appraisal of learning, as the teacher is more focused on the formality of the act than on the student's teaching process. It is needed to consider that the way in which learning takes place is the result of processes that are always unique and personal. Therefore, this work believes that didactic pluralism, which consists of using several methodological resources to serve all students, and not a portion of them, may be the most efficient and least abstract way of teaching science. Thus, the main objective of this work was to investigate the contributions of didactic pluralism in the classroom. The research was carried out in a private school in the municipality of Santa Maria, RS, in the period 2017-2018. In 2017, two classes from the 7th year of elementary school participated in this study, totaling 44 students. In the following year, in 2018, three classes, totaling 68 students, also from the 7th year of elementary school, collaborated for this study. Thus, this work comprises action research with a qualitative approach. The instruments for data collection were: questionnaires; teacher's field diary; photos and footage of the classes. The results revealed that didactic pluralism contributed to the learning of science content developed in these classes, even when students were evaluated after 8 months of interventions. In addition, the activities developed generated motivation in the students, evidenced by the observations in classes and by the students' own reports. The possibility of teacher and student interaction was also demonstrated through the joint reflection of the questioning about hypotheses, concepts and doubts, which emerged during the development of didactic activities, thus contributing to an investigative assessment of the teaching and learning process. In addition, writing about the lived experience can collaborate considerably by consolidating professional identity and improving the action of teachers, especially when taking into account the importance of several factors involved in education.